Improving three-dimensional human pluripotent cell culture efficiency via surface molecule coating - Li, Qiang; Pan, Ying; Han, Li; Yang, Yakun; Wu, Xinran; Lei, Yuguo (Frontiers in Chemical Engineering, 2022)
Human pluripotent stem cells (hPSCs) are ideal “raw materials” for making various human cell types for regenerative medicine and are needed in large numbers. 3D suspension culturing (e.g., stirred-tank bioreactor or STR), which suspends and cultures cells in an agitated medium, has been extensively studied to scale up hPSC production. However, a significant problem with 3D suspension is the uncontrolled spheroid agglomeration. It leads to cell growth arrest, cell apoptosis, and inhomogeneity in cell purity and quality. We propose that i) inhibiting the spheroid adhesion can prevent spheroid agglomeration and ii) the inhibition can be achieved via coating spheroids with biocompatible anti-adhesion molecules. We used PEG-lipids as model anti-adhesion molecules to successfully demonstrate the concept. PEG-lipids anchor to the spheroid surface through the interactions between their lipid chains and the cell membrane lipids. The flexible and hydrophilic PEG chains act as a dynamic barrier to prevent spheroid adhesion. We showed that the coating eliminated spheroid agglomeration, leading to homogenous spheroid size distribution and significant improvements in cell growth rate and volumetric yield. This novel approach is expected to impact large-scale hPSC production significantly. Furthermore, the approach can be generalized for culturing other human cell types.